Contribution of Intestinal Barrier Damage, Microbial Translocation and HIV-1 Infection Status to an Inflammaging Signature - Steele, Amanda K.; Lee, Eric J.; Vestal, Brian; Hecht, Daniel; Dong, Zachary; Rapaport, Eric; Koeppe, John; Campbell, Thomas B.; Wilson, Cara C. (PloS one, 2014)
Systemic inflammation is a characteristic of both HIV-1 infection and aging ("inflammaging"). Intestinal epithelial barrier damage (IEBD) and microbial translocation (MT) contribute to HIV-associated inflammation, but their impact on inflammaging remains unclear. Plasma biomarkers for IEBD (iFABP), MT (LPS, sCD14), T-cell activation (sCD27), and inflammation (hsCRP, IL-6) were measured in 88 HIV-1 uninfected (HIV(neg)) and 83 treated, HIV-1-infected (HIV(pos)) adults from 20-100 years old. Age positively correlated with iFABP (r = 0.284, p = 0.008), sCD14 (r = 0.646, p = <0.0001) and LPS (r = 0.421, p = 0.0002) levels in HIV(neg) but not HIV(pos) subjects. Age also correlated with sCD27, hsCRP, and IL-6 levels regardless of HIV status. Middle-aged HIV(pos) subjects had elevated plasma biomarker levels similar to or greater than those of elderly HIV(neg) subjects with the exception of sCD14. Clustering analysis described an inflammaging phenotype (IP) based on iFABP, sCD14, sCD27, and hsCRP levels in HIV(neg) subjects over 60 years of age. The IP in HIV(neg) subjects was used to develop a classification model that was applied to HIV(pos) subjects to determine whether HIV(pos) subjects under 60 years of age were IP+. HIV(pos) IP+ subjects were similar in age to IP- subjects but had a greater risk of cardiovascular disease (CVD) based on Framingham risk score (p =  0.01). We describe a novel IP that incorporates biomarkers of IEBD, MT, immune activation as well as inflammation. Application of this novel IP in HIV-infected subjects identified a group at higher risk of CVD.